Anomalous resistivity and superconductivity in the two-band Hubbard model with one narrow band (Review Article): Сверхпроводимость - Kagan, M.Yu.; Valkov, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We search for marginal Fermi-liquid behavior in the two-band Hubbard model with one narrow band. We consider the limit of low electron densities in the bands and strong intraband and interband Hubbard interactions. We analyze the influence of electron–polaron effect and other mechanisms of mass-enhancement (related to momentum dependence of the self-energies) on effective mass and scattering times of light and heavy components in the clean case (electron–electron scattering and no impurities). We find the tendency towards phaseseparation (towards negative partial compressibility of heavy particles) in a 3D case for large mismatch between the densities of heavy and light bands in a strong coupling limit. We also observe that for low temperatures and equal densities the resistivity in a homogeneous state R(T) T 2 behaves in a Fermi-liquid fashion both in 3D and 2D cases. For temperatures higher then effective bandwidth for heavy electrons T > Wh* the coherent behavior of heavy component is totally destroyed. The heavy particles move diffusively in the surrounding of light particles. In the same time the light particles scatter on the heavy ones as if on immobile (static) impurities. In this regime the heavy component is marginal, while the light one is not. The resistivity goes on saturation for T > Wh* in the 3D case. In 2D the resistivity has a maximum and localization tail due to weak-localization corrections of Altshuler–Aronov type. Such behavior of resistivity in 3D could be relevant for some uranium-based heavy-fermion compounds like UNi2Al3 and in 2D for some other mixed-valence compounds possibly including the layered manganites. We also consider briefly the superconductive (SC) instability in the model. The leading instability is towards p-wave pairing and is governed by enhanced Kohn–Luttinger mechanism of SC at low electron density. The critical temperature corresponds to the pairing of heavy electrons via polarization of the light ones in 2D.